Greatest Lower Bounds of System Failure Probability in a Time Interval Under Incomplete Information About the Distribution Function of the Time to Failure - Stoikova, L. S. (Cybernetics and systems analysis, 2015)
The greatest lower bounds are obtained for the probability F ( υ ) − F ( u ), 0 < u < υ < ∞ , in the class of distribution functions F ( x ) of nonnegative random variables with unimodal density with mode m<u and two first fixed moments.